COMPONENTS OF RUSSIAN CULINARONYMS, COMBINATION OF CULINARY AND LANGUAGE - Tolibjonova Surayo (Лучшие интеллектуальные исследования, 2024)
The purpose of this study is to point out the components in modern Russian culinaronyms. This work also presents components’ characteristics as a theoretical part for naming food. We have used the qualitative descriptive method to find out the components included in Russian culinaronyms. The results of this study indicate that there are a number of components in modern Russian food names such as culinary group (gathering a number of components related to cooking), human, time, and freedom (or author component). Moreover, these elements can be identified with the help of different language tools. This research moreover reveals that one lexicon can constitute rotated component or doubled-component. The result of the study can be used by students and specialists in courses of lexicology and linguoculture. Besides, this study contributes to the stylistic features of culinary text type. This research focuses on systematizing components in Russian culinaronyms, introducing the new concept of ‘culinaronym component’ and its general qualities based on the combination of culinary and language.